2016
DOI: 10.1177/2165079916662050
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Structure as a Determinant of Job Burnout

Abstract: This exploratory study determined the impact of organizational structure, particularly participation in decision making, instrumental communication, formalization, integration, and promotional opportunity, on burnout among Pakistani pediatric nurses. Data were collected from pediatric nurses working for Punjab's largest state-run hospital. The findings revealed that participation in decision making, instrumental communication, and promotional opportunity prevented burnout. Formalization contributed to burnout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
(112 reference statements)
3
16
0
Order By: Relevance
“…Favrod et al [45] found NICU nurses reported more traumatic stressors in their working environment. Pediatric nursing workplaces with a strict structure of rules and regulations [33] or nurse leaders who valued structure over staff considerations [41] were found to have nurses with higher burnout. Nurses who had higher perceived organizational support had lower burnout [39].…”
Section: Work Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Favrod et al [45] found NICU nurses reported more traumatic stressors in their working environment. Pediatric nursing workplaces with a strict structure of rules and regulations [33] or nurse leaders who valued structure over staff considerations [41] were found to have nurses with higher burnout. Nurses who had higher perceived organizational support had lower burnout [39].…”
Section: Work Environmentmentioning
confidence: 99%
“…Systems issues such as overwhelming clerical work, administrative, and resource issues have impacts on provider burnout in both the pediatric nurse and general physician populations [36,56,65,121]. Poor leadership is associated with pediatric nurse burnout as identified by Bilial and Ahmed [33] and Druxbury et al [41]; this 88…”
Section: Work Environmentmentioning
confidence: 99%
See 3 more Smart Citations